Bilastine: a new antihistamine with an optimal benefit-to-risk ratio for safety during driving. Issue 1 (2nd January 2016) - Jáuregui, Ignacio; Ramaekers, Johannes G; Yanai, Kazuhiko; Farré, Magí; Redondo, Esther; Valiente, Román; Labeaga, Luis
Abstract : Introduction : Rational selection of a second-generation H1 -antihistamine requires efficacy and safety considerations, particularly regarding central nervous system (CNS) effects (cognitive and psychomotor function), potential for driving impairment, minimal sedative effects and a lack of interactions. This review evaluates the key safety features of the non-sedating antihistamine, bilastine, during driving and in preventing road traffic accidents. Areas covered : Among the second-generation H1 -antihistamines, sedative effects which can affect cognitive and psychomotor performance, and possibly driving ability, may not be similar. Bilastine is absorbed rapidly, undergoes no hepatic metabolism or cytochrome P450 interaction (minimal drug–drug interaction potential), and is a substrate for P-glycoprotein (limiting CNS entry). Positron emission tomography showed that, compared with other second-generation H1 -antihistamines, bilastine has the lowest cerebral histamine H1 -receptor occupancy. Bilastine 20 mg once daily (therapeutic dose) is non-sedating, does not enhance the effects of alcohol or CNS sedatives, does not impair driving performance and has at least similar efficacy as other second-generation H1 -antihistamines in the treatment of allergic rhinoconjunctivitis and urticaria. Expert opinion : Current evidence shows that bilastine has an optimal benefit-to-risk ratio, meeting all conditions for contributing to safety in drivers who need antihistamines, and hence for being considered as an antihistamine of choice for drivers.